1993
DOI: 10.1007/bf01351838
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid composition and arachidonic acid concentrations in alveolar bone of rats fed diets with different lipids

Abstract: The purpose of the present study was to determine if the type of dietary fat can modify the fatty acid composition and arachidonic acid levels in the alveolar bone phospholipids. Three groups of rats were fed nutritionally adequate semipurified diets containing different lipids: 10% corn oil (control, group I, rich in n-6 fatty acids); 9% butter + 1% corn oil (experimental, group II, rich in saturated fatty acids); and 9% ethyl ester concentrate of n-3 fatty acids + 1% corn oil (experimental, group III, rich i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
2

Year Published

1993
1993
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 10 publications
1
14
0
2
Order By: Relevance
“…The work of Alam et al [2] evaluated the fatty composition of arachidonic acid in the alveolar bone of laboratorial rats and concluded that specific dietary lipids altered the fatty acid composition of bone lipids, and added that diets enriched with fish oil decreased the concentration of arachidonic acid by diminishing the amount of osteoclasts in the area investigated. Arachidonic acid can be converted to series 2 prostaglandins or to series 4 leukotriens by ciclooxy-genase pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The work of Alam et al [2] evaluated the fatty composition of arachidonic acid in the alveolar bone of laboratorial rats and concluded that specific dietary lipids altered the fatty acid composition of bone lipids, and added that diets enriched with fish oil decreased the concentration of arachidonic acid by diminishing the amount of osteoclasts in the area investigated. Arachidonic acid can be converted to series 2 prostaglandins or to series 4 leukotriens by ciclooxy-genase pathways.…”
Section: Discussionmentioning
confidence: 99%
“…These dietary-mediated changes in femur lipids following high n-3 or n-6 PUFA or low ratio of n-6:n-3 PUFA diets results in stronger bones [1], increased bone formation rates [3,7], higher bone mineral content [5], and higher bone mineral density [3,5,7,8]. Interestingly, bone lipids influenced by dietary ratio of n-6:n-3 PUFA included polar (PL; associated with cellular membranes) and/or neutral [common storage form of lipids, or specifically triacylglycerols (TAG)] measured in femur and alveolar bones [3][4][5]. The bone lipid pool affected is of interest as it has been suggested that a greater amount of n-3 PUFA in bone cell membranes may reduce the availability of n-6 PUFA, specifically arachidonic acid, and thereby attenuate osteoclastogenesis [9].…”
Section: Introductionmentioning
confidence: 96%
“…Alternatively, high n-3 and n-6 PUFA diets (20 % by weight for 65 days) [1], or differing ratios of n-6:n-3 PUFA (7-10 % by weight for 6-10 weeks) [3][4][5], resulted in lower SFA and higher PUFA in the femur of developing male rats. These dietary-mediated changes in femur lipids following high n-3 or n-6 PUFA or low ratio of n-6:n-3 PUFA diets results in stronger bones [1], increased bone formation rates [3,7], higher bone mineral content [5], and higher bone mineral density [3,5,7,8].…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations